2014
DOI: 10.1021/pr5006058
|View full text |Cite
|
Sign up to set email alerts
|

Intact Protein Analysis of Ubiquitin in Cerebrospinal Fluid by Multiple Reaction Monitoring Reveals Differences in Alzheimer’s Disease and Frontotemporal Lobar Degeneration

Abstract: The impairment of the ubiquitin-proteasome system (UPS) is thought to be an early event in neurodegeneration, and monitoring UPS alterations might serve as a disease biomarker. Our aim was to establish an alternate method to antibody-based assays for the selective measurement of free monoubiquitin in cerebrospinal fluid (CSF). Free monoubiquitin was measured with liquid chromatography-multiple reaction monitoring mass spectrometry (LC-MS/MS) in CSF of patients with Alzheimer's disease (AD), amyotrophic lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 27 publications
5
52
2
Order By: Relevance
“…bvFTD, nfvPPA, and svPPA. Recent studies investigating the AD biomarker panel in FTD subtypes reported inconsistent results about Ab42 concentration in CSF of nfvPPA patients compared with svPPA and bvFTD (increased, unchanged) but are in agreement that Tau and pTau181 were not different (Borroni et al 2014;Oeckl et al 2014;Santangelo et al 2015). Unchanged pTau181 concentrations between the FTD subtypes have also been observed in previous studies, but data about Ab42 and Tau are inconsistent (Pijnenburg et al 2006;Bibl et al 2007aBibl et al , 2011de Souza et al 2011;Landqvist et al 2013;Scherling et al 2014) indicating that the AD biomarker panel is not suitable for the differential diagnosis of FTD subtypes.…”
Section: Differential Diagnosis Within the Ftd Spectrummentioning
confidence: 86%
See 3 more Smart Citations
“…bvFTD, nfvPPA, and svPPA. Recent studies investigating the AD biomarker panel in FTD subtypes reported inconsistent results about Ab42 concentration in CSF of nfvPPA patients compared with svPPA and bvFTD (increased, unchanged) but are in agreement that Tau and pTau181 were not different (Borroni et al 2014;Oeckl et al 2014;Santangelo et al 2015). Unchanged pTau181 concentrations between the FTD subtypes have also been observed in previous studies, but data about Ab42 and Tau are inconsistent (Pijnenburg et al 2006;Bibl et al 2007aBibl et al , 2011de Souza et al 2011;Landqvist et al 2013;Scherling et al 2014) indicating that the AD biomarker panel is not suitable for the differential diagnosis of FTD subtypes.…”
Section: Differential Diagnosis Within the Ftd Spectrummentioning
confidence: 86%
“…Neurogranin is a post-synaptic protein and is implicated in synaptic plasticity and learning (Janelidze et al 2016) and may improve the differentiation of FTD and AD when used in combination with Ab42, Tau, and pTau181. We recently observed a 40% increased CSF ubiquitin concentration in AD compared with FTLD patients (Oeckl et al 2014). As indicated by the calculated sensitivity (100%) and specificity (53%) values, ubiquitin alone does not improve differential diagnosis of AD and FTD, but it might be advantageous in combination with other biomarkers as described above.…”
Section: Differential Diagnosis Of Ftd To Other Dementiasmentioning
confidence: 95%
See 2 more Smart Citations
“…simultaneous quantification of ␤Syn and ␥Syn. MRM has already successfully been applied for the determination of biomarker candidates in CSF (12). In addition, it allows a more detailed characterization of the whole protein regarding truncations or PTMs by analyzing several peptides across the protein sequence after proteolytic digestion and ␣Syn PTMs are in discussion as promising biomarker candidates in synucleinopathies (13).…”
Section: ␣-Synuclein (␣Syn)mentioning
confidence: 99%